An engraved tooth pendant from Donkalnis, western Lithuania : a rare discovery in a Mesolithic burial - Butrimas, Adomas; Irsenas, Marius; Macane, Aija; Mannermaa, Kristiina; Nordqvist, Kerkko; Rimkus, Tomas (Cambridge University Press, 2025)
A re-examination of animal tooth pendants from Mesolithic (c. 9000-5000 BC in Lithuania) graves at Donkalnis (western Lithuania) revealed one engraved specimen. Among the hundreds of pendants reported for this period in the eastern Baltic, engravings are rare. The discovery offers new insights into the human-animal relationships reflected in northern forager burial traditions. Peer reviewed